Factors associated with adolescent cigarette smoking in Greece: Results from a cross sectional study (GYTS Study) - Gourgoulianis Konstantinos; Kyrlesi Athina; Siziya Seter; Rudatsikira Emmanuel; Muula Adamson S; Rachiotis George; Hadjichristodoulou Christos (BMC, 2008)
Abstract Background Data about the predictors of smoking among adolescents in Greece are sparse. We tried to identify factors associated with current cigarette smoking among in-school adolescents in Greece in the context of GYTS study. Methods A secondary analysis of data from a questionnaire study using the Global Youth Tobacco Survey methodology was conducted to identify factors associated with smoking among adolescents in Greece. Data were collected in 2004-2005. The outcome variable was cigarette smoking within the past 30 days preceding the survey while independent variables included age, gender, parental educational status, parental smoking, perception of harmfulness of smoking, and the amount of pocket money at the adolescent's disposal. Results 6141 adolescents (51.5% males and 48.5% females) participated in the study. In multivariate analysis, cigarette smoking was associated with male gender (OR: 1.62; 95% CI: 1, 08-3.08), parental smoking (OR: 2.59; 95% CI: 1.45-5.89), and having pocket money ≥ 16 Euros (OR: 2.64; 95% CI: 1.19-5.98). Conclusion Male gender, parental smoking, and having pocket-money ≥ 16 Euros were independently associated with current smoking among Greek students. These findings could be taken into account in order to formulate a comprehensive anti-smoking strategy in Greece.